Measuring women's economic empowerment Time use data and gender inequality - Ferrant, Gaëlle (OECD Publishing, 2019)
Empowerment, co-ordinated jointly by the OECD Development Co-operation Directorate, the Development Centre and Statistics Directorate. The initiative aims to identify policy and programme solutions to promote women's economic empowerment by recognising, reducing and redistributing women's unpaid care work. This paper presents new analysis of time use data and unpaid care work from Bangladesh, Ethiopia, Peru and South Africa as well as comparisons with OECD countries. It provides recommendations for policy makers, donors and development practitioners to support the achievement of the Sustainable Development Goals, drawing on learning from the Social Institutions and Gender Index and in-country research by the OECD Policy Dialogue on Women's Economic Empowerment. Specifically, the recommendations focus on how to recognise unpaid care work by measuring and valuing it, reduce time spent on drudgery by the provision of quality infrastructure and redistribute unpaid care tasks more equally between men and women by transforming gender stereotypes
Keywords: Development